Preparation and analgesic activity test of Capsicum frutescens oleoresin - Do, Hoang Minh Vo; Xuan, Le Tien; Vo, Mong Tham; Huynh, Bui Thong; Nguyen, Dinh Tien Dung; Thi, Thuy Anh Nguyen; Truong, Cong Tri; Nguyen, Dai Hai (Vietnam Journal of Science and Technology, 2021)
Capsaicin is an alkaloid in capsaicinoids group known as a spicy flavour ingredient in chilies and some pungent foods. Recently, capsaicin has been used not only as an additive in food but also as a medicine like analgesic, anticancer, and antidiabetic drug due to its’ pharmacological properties. In this study, capsicum oleoresin was extracted via heating chili powder, Capsicum frutescens (L.), with ethanol 80% at 70 °C in 120 minutes, then the extract was solvent evaporated in low pressure. Capsaicin was determined by thin-layer chromatography (TLC) and qualified by high-performance liquid chromatography (HPLC) method. Finally, the analgesic activity of capsicum oleoresin was tested on mice. The results show that capsicum oleoresin extracted from 2 kilograms of capsicum powder was 368.84 grams with 2.84% capsaicin. The central analgesic and peripheral analgesic effects of capsicum oleoresin were 90 minutes and 10-15 minutes after treatment, respectively.